Profile of the street children in Iloilo City. - Tan, Rhodora Gail F
This study attempts to provide base line data on the conditions and way of life of streetchildren in Iloilo City. The repondents of this study were 61 children interviewed in the City Proper area. The location was selected because this is were street urchins have been observed to frequent. The researcher used the interview schedule as the principal method of gathering data. Purposive sampling was used because there was a conflict as to the exact number of street children, as reported by the different concerned agencies., Mostly older children were included in the study. There were more boys and girls. The average educational attainment is low - pegged at the level of Grade II. It was found that street life significantly affects the weakening of the child's ties with the home, by lessening the contact between him and his parents. Children take to the streets primarily because of poverty. Most of them report to being engage in economic activity which are generally legitimate. The conditions of street life are rife with adverse influences, risks, hazards and difficulties which the children must cope with in order to effectively adapt to this environment. For most aspects of street life, the respondents exhibited apathy by accepting it as the way it is. In some areas, however, they found that they have to be active agents in making the situation more tolerable or bearable for them, hence, the tendency to earn money if only to have some for their personal needs. Finally, ranked among the highest aspirations of the street children are the pursuit of education and the desire for careers which would permit them to carry guns or have physical skills that they could use in order to defend themselves.